Triazine-based covalent organic polymers: design, synthesis and applications in heterogeneous catalysis. Issue 42 (7th October 2016) - Puthiaraj, Pillaiyar; Lee, Yu-Ri; Zhang, Siqian; Ahn, Wha-Seung
Abstract : The development of triazine-based COPs using different building blocks or alternative synthetic chemical reactions and their potential application in heterogeneous catalysis. Abstract : Triazine-based covalent organic polymers (COPs) constructed from triazine or nitrile containing precursors via covalent bonding are becoming an important sub-class of porous organic framework materials for a range of applications. In particular, these materials have been proposed as a new catalyst or support material for a variety of liquid phase organic transformation reactions owing to their tunable porous structures with high surface area, high nitrogen contents, high stability in both organic and aqueous media, and relatively easy synthesis. This review article summarizes the current research activities devoted to the synthesis and characterization of new triazine-based COP materials, and their applications for heterogeneous catalysis aiming at fine chemicals synthesis are presented with critical comments.